A középkori jogászok méltányosságról, igazságosságról és jogról alkotott felfogása - Frivaldszky János (DÍKÉ: A MÁRKUS DEZSŐ ÖSSZEHASONLÍTÓ JOGTÖRTÉNETI KUTATÓCSOPORT FOLYÓIRATA, 2025)
The medieval jurists believed that equity was inherent in the nature of things, as an immanent order and harmony which the emperor, or the judge or jurist, had to transform by his will, by the act of justice, into a legal norm, a prescription. Thus, by will, justice becomes a prescribed rule. Just as equity is the source and source of justice, the latter plays the same role with regard to the individual legal norms. Although jurisprudence has been confined to the texts, the numerous references to equity found in them have left sufficient space to adapt the corpus of law, which is regarded as unconditional autho-rity, to new circumstances. As far as the practical legal justification of servitude and private property was concerned, the natural law norms of freedom for all men and the common possession of goods continued to be valid, but only as guidelines rather than as binding legal norms of the natural law.